Playback-elicited heterospecific aggressive responses in urbanized Sparkling Violetear are modulated in relation the risk of take-over hypothesis - Tellería, Luciana; Garitano-Zavala, Álvaro (Frontiers in Ecology and Evolution, 2024)
Hummingbirds have crucial ecological importance in natural and human-altered habitats in the Neotropics. Their unique biological characteristics imply a delicate energetic balance that drove the evolution of species-specific dominance and territorial behavior tactics that, in turn, shape the diversity and composition of nectarivorous communities. Understanding these factors could help improve conservation strategies, particularly important for eroding communities in cities. Our objective is to evaluate whether a species of territorial hummingbird, the Sparkling Violetear (Colibri coruscans), is able to modulate its aggressive behavior in relation to the identity of the species that invades its feeding territory, comparing between dry (relative depletion of nectar resources) and wet seasons, and analyzing the possible ecological factors that determine this response. Considering the maximization of energy efficiency, we hypothesize that the territorial aggressive responses of Sparkling Violetears will vary in relation to the territoriality and behavioral dominance of each intruder species, and that aggressive responses in the dry season will be greater compared to the wet season. We elicited aggressive behavioral responses with territorial songs playbacks from the four species that compose the urban nectarivorous bird community, including songs from their own species, characterizing eight behaviors that varied in aggressive intensity. We quantified the aggressive response in two ways: the number of observation events in which territorial Sparkling Violetears performed each behavior and by constructing an “aggressiveness score” for each territorial individual in each observation event. Territorial aggressive response varied significantly in relation to the identity of the intruding species, but the seasonal effect was only observed, as a more aggressive response in the dry season, towards heterospecific playbacks. We analyzed several hypotheses that could explain the species-specific aggressive response, concluding that the “risk to take-over” hypothesis, through wing morphology and maneuverability, best explains the modulation of the aggressive response in relation to the territoriality and behavioral dominance of each intruder species. These results are useful for urban planning if we elucidate the ecological conditions that could promote the coexistence of subordinate species with dominant ones.